2002
DOI: 10.1159/000054727
|View full text |Cite
|
Sign up to set email alerts
|

Marked Increases in Macrophage Colony-Stimulating Factor and Interleukin-18 in Maintenance Hemodialysis Patients: Comparative Study of Advanced Glycation End Products, Carboxymethyllysine and Pentosidine

Abstract: Background: Recent studies have demonstrated the crucial involvement of advanced glycation end products (AGEs) in major complications of long-term hemodialysis (HD) patients. HD, in a clinical setting, is characterized by increased production of proinflammatory cytokines. AGEs and cytokines are presumed to be responsible for the development of major complications in long-term HD. We therefore investigate here the relationship between a newly identified cytokine, interleukin-18 (IL-18), and two AGEs, carboxymet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Our observations are compatible with the fi ndings of Gangemi et al [15] and Uchimura et al [16] . Considering their reports and our fi ndings, several possible mechanisms might contribute to this high IL-18 level.…”
Section: Discussionsupporting
confidence: 94%
“…Our observations are compatible with the fi ndings of Gangemi et al [15] and Uchimura et al [16] . Considering their reports and our fi ndings, several possible mechanisms might contribute to this high IL-18 level.…”
Section: Discussionsupporting
confidence: 94%
“…All are characterized by chronic inflammation as is observed in patients with uremia [17,18]. Gangemi et al [7] and Uchimura et al [19] have shown that plasma levels of IL-18 are elevated in patients undergoing hemodialysis. In the current work, we demonstrate that plasma IL-18 concentrations are raised in patients with CRF and those undergoing CAPD (table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma IL-18 levels are present in a number of inflammatory diseases, including rheumatoid arthritis, Crohn's disease, atherosclerosis [26] and CKD [27] . IL-18 levels have been shown to be increased in predialysis, HD and peritoneal dialysis (PD) patients [23,26,28,29] . As increased production of IFN-␥ is one of the main characteristics of the Th1 response, IL-18 accumulation in uremic patients may contribute to such a response also in HD patients [26,30] .…”
Section: Interleukin-18mentioning
confidence: 99%